Hubungan Tingkat Kekerapan Mengkonsumsi Kopi Dengan Kejadian Dispepsia Di Puskesmas Kartasura - Husna Kamila, Arinil; , dr.Sigit Widyatmoko, Sp.PD.,M.Kes; , dr. Safari Wahyu Jatmiko (2016)
Background: One of the risk factors that cause dyspepsia include caffeine consumption. Caffeine is commonly found in products such as coffee drinks can cause increase secretion of gastrin so that it will stimulate the production of stomach acid. The high acid cause inflammation and erosion of the gastric mucosa so that it can bring dyspeptic disorders. Objective: The purpose of execution of this study was to determine the correlation between the frequency of coffee consumption and the incidence of dyspepsia. Methods: This study was an observationalcross sectionalanalytic approach, conducted in February-March 2016 on 62 samples went to a primary care unit in Pabelan, Kartasura. Technique sampling in this study using aConsecutive Sampling. Retrieval of data from the study sample using a questionnaire containing variable frequency level of coffee consumption and dyspepsia. Analysis of test data using Koefisien Kontigensiwith univariate analysis and variat. Results: The results of the statistical testp= 0,3. p value >0.05 means that it's notsignificant relationship between the two variables. Conclusion: From this study it can be concluded that there is a negative correlation between consumed coffee with dyspepsia. Keywords: Consuming coffee, dyspepsia, caffeine